2019
DOI: 10.1371/journal.pone.0220970
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of unintended pregnancy in sub-Saharan Africa: A multi-country analysis of demographic and health surveys

Abstract: Introduction Approximately 14 million unintended pregnancies are recorded annually in sub-Saharan Africa (SSA). We sought to investigate the prevalence and determinants of unintended pregnancies among women in sub-Saharan Africa. Materials and methods The study pooled data from current Demographic and Health Surveys (DHS) conducted from January 1, 2010 to December 31, 2016 from 29 countries in SSA. Logistic regression analysis was used to examine the factors that influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
173
8
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(208 citation statements)
references
References 49 publications
23
173
8
4
Order By: Relevance
“…The results of the analysis found that women who live in urban areas are more likely than women who live in rural areas to experience an unintended pregnancy. This information contradicts previous research in Pakistan, Ethiopia and several countries in sub-Saharan Africa that informs that living in rural areas is a risk factor for unintended pregnancy in women compared to women living in urban areas [9][10][11] . In the Indonesian context, the availability of health facilities is better in urban areas than rural areas 12,13 , including the availability of contraceptives.…”
Section: Discussioncontrasting
confidence: 94%
“…The results of the analysis found that women who live in urban areas are more likely than women who live in rural areas to experience an unintended pregnancy. This information contradicts previous research in Pakistan, Ethiopia and several countries in sub-Saharan Africa that informs that living in rural areas is a risk factor for unintended pregnancy in women compared to women living in urban areas [9][10][11] . In the Indonesian context, the availability of health facilities is better in urban areas than rural areas 12,13 , including the availability of contraceptives.…”
Section: Discussioncontrasting
confidence: 94%
“…From these, 18,468 (8,644 in the 2005 EDHS and 9,824 in the 2016 EDHS) were married or in-union. Women who were pregnant at the time of the survey (2,191), single, divorced and widowed women were excluded from the analysis. The reason for this is that information about contraceptive use among unmarried (never married, widowed or divorced) women is less reliable due to social desirability bias.…”
Section: Data Sourcementioning
confidence: 99%
“…A multi-country analysis of DHS data from Sub-Saharan counties identified that 29% of married women had unintended pregnancy ranging from 10.8% in Nigeria to 54. 5% in Namibia [2]. The 2016 Ethiopian demographic and health survey (EDHS) report identified that 25% of births in Ethiopia were unintended (8% unwanted and 17% mistimed) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa (SSA), women of reproductive age bear a disproportionate burden of unintended pregnancies and sexually transmitted infections (STIs) including human immunodeficiency virus (HIV) [1]. In SSA, an estimated 29% of pregnancies are unintended [2]. Moreover, women account for approximately 56% of all adults living with HIV in this region [3].…”
Section: Introductionmentioning
confidence: 99%